Regulating stem cell fate within microenvironmental niches - Buglass, SK (2014)
Improving the repopulation potential of human umbilical cord blood (UCB) haemopoietic stem cells (HSCs) remains a paramount goal in HSC transplantation (HSCT) therapy. This implies enhancing the homing and engraftment potential of UCB-CD34+CD133+ cells to the bone marrow (BM). Although an array of molecules continues to be identified as ‘key’ homing molecules, the molecular mechanisms controlling HSC homing are still not fully understood. The regulatory implications of hypoxia in the BM, with the concomitant stabilisation of hypoxia inducible transcription factor-1α (HIF-1α), are becoming more apparent, yet at the commencement of this thesis no study had explored whether hypoxia induced signalling can be adopted to regulate the homing and engraftment of transplanted HSCs. The aim of this DPhil project was thus to investigate whether hypoxic conditions as detected in the BM influence the adhesion of UBC-CD133+ cells to osteoblasts, BM stromal cells and BM endothelial cells-60 (BMEC-60), as well as their transmigration towards chemokine SDF-1α across BMEC-60. Increasing the exposure of UCB-CD133+ cells to 1.5% O2 doubled the percentage of transmigrating cells (p<0.05), and while hypoxia stimulated UCB-CD133+ cells preferentially adhered to IL-1β stimulated BMEC-60, their adhesion to non-stimulated (BMEC-60) was significantly improved (p<0.001). To help unravel the underlying molecular mechanisms, we attempted to examine the potential involvement of hypoxia regulated scaffolding protein HEF-1/NEDD9/Cas-L (HEF-1) in the increased percentage of migrating UCB-CD133+ cells after hypoxia pre-conditioning. The role of HEF-1 in HSCs is unexplored, and its multifunctional contribution in a variety of processes including cell migration, attachment and invasion make HEF-1 a prime candidate as a contributing homing molecule. After identifying a suitable short-hairpin RNA (shRNA) sequence to knockdown HEF-1, generating lentiviral (LV)-particles in house and optimising transduction protocols, HEF-1 knockdown was achieved in haemopoietic model cell lines KG-1 and KG-1A (KG-1/KG-1A–HEF1). Significantly decreased KG-1A–HEF1 cell adhesion to non-stimulated BMEC-60 was detected. Together, these studies provide a promising platform to further explore the role of HEF-1 in hypoxia induced UCB-CD133+ cell transmigration towards the key homing molecule SDF-1α.